Criteria-Based Assessment Of Creative Types Of Writing In A Form Of Essay - Gaziza Otarbayeva, Zhazira Muldyyeva, Zhadyra Shaimerdenova, Kuralay Mukhamadi, Kanat Ibragimov, (Opción, 2019)
The aim of the study is to investigate criteria-based assessment of creative types of writing in a form of essay via comparative qualitative research methods. As a result, the progress is the most evident on the creativity dimension, as students made a significant improvement in their use of similes and detailed descriptions. Results of the post-experimental stage of the research brought us to the conclusion that students acquired the basic techniques of essay composition (logical structure, theme development, author’s voice, originality in the choice of vocabulary).